Studies of Vitamin B12 Metabolism in Patients with Chronic Hepatitis and Liver Cirrhosis - Spârchez, T.; Gheorghescu, B.; Jovin, Gh.; Merculiev, Elena (Nuklearmedizin - NuclearMedicine, 1968)
We have studied the kinetiks of vitamin B12 and especially the liver compartment, in 28 normals and 76 patients with chronic hepatitis and liver cirrhosis.The study was carried out by means of vitamin B1258Co, administered per os (alone or followed by “flushing dosis”), vitamin B1257Co administered intravenously and by double tracer technique.Our results indicate the Pertubation of intrahepatic storage compartment of radiocobalamine, in patients with chronic hepatitis and especially in patients with active hepatitis and in cirrhotics.This deficiency can be explained probably, by an alteration of the transport to the liver of the absorbed vitamin B12, by an inadequate chemical forme, by hepatic enzymatic disturbances or by excessive handling and storage in extrahepatic compartment.